2022
DOI: 10.3390/cancers14122955
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis and Therapeutic Potential of Leukemia Inhibitory Factor in Cancer Cachexia

Abstract: Cachexia is a chronic metabolic syndrome that is characterized by sustained weight and muscle mass loss and anorexia. Cachexia can be secondary to a variety of diseases and affects the prognosis of patients significantly. The increase in inflammatory cytokines in plasma is deeply related to the occurrence of cachexia. As a member of the IL-6 cytokine family, leukemia inhibitory factor (LIF) exerts multiple biological functions. LIF is over-expressed in the cancer cells and stromal cells of various tumors, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…In our study, LIF was detected in culture supernatants of SLC cells and tumor extracts of SLC-transplanted rats, and in the rats' sera at low levels. LIF is a member of the IL-6 superfamily and is characterized by the use of the common receptor chain glycoprotein 130 and activates the Janus kinase-signal transducer and activator of transcription signaling pathway [38]. A recent study showed that mice transplanted with colon 26 cells exhibited LIF-dependent muscle atrophy, despite having a substantially low blood concentration of LIF (approximately 10 pg/mL) [39].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, LIF was detected in culture supernatants of SLC cells and tumor extracts of SLC-transplanted rats, and in the rats' sera at low levels. LIF is a member of the IL-6 superfamily and is characterized by the use of the common receptor chain glycoprotein 130 and activates the Janus kinase-signal transducer and activator of transcription signaling pathway [38]. A recent study showed that mice transplanted with colon 26 cells exhibited LIF-dependent muscle atrophy, despite having a substantially low blood concentration of LIF (approximately 10 pg/mL) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) has also been identified as a potential factor that interacts with TNF-α or acts independently to induce systemic inflammation in the context of cancer cachexia [76,77]. Multiple types of cancer have been associated with this particular interleukin, and proinflammatory cytokines that originate from the host, such as IL-1, have the potential to amplify its effects [9].…”
Section: Muscle Atrophymentioning
confidence: 99%
“…While these pathways collectively contribute to cellular differentiation, survival and self-renewal, the qualitative and quantitative contributions of individual pathways are cell-type specific, leading to the pleiotropic effects of LIF ( Nicola and Babon, 2015 ). Although named for its ability to inhibit proliferation of a myeloid leukemia cell line by inducing its terminal differentiation into macrophages ( Gearing et al., 1987 ), LIF also regulates the growth and differentiation of embryonic stem cells ( Smith et al., 1988 ; Williams et al., 1988 ), peripheral neurons ( Murphy et al., 1991 ; Li et al., 1995 ; Cheng and Patterson, 1997 ), osteoblasts ( Matsushita et al., 2014 ; Sims, 2020 ), adipocytes ( Guo et al., 2021 ; Zeng et al., 2022 ), hepatocytes ( Baumann and Wong, 1989 ), and endothelial cells ( Ferrara et al., 1992 ; Li et al., 2022 ). This multifarious property of LIF has led to several rediscoveries of the protein and a variety of synonyms have been used in the older literature ( Alexander et al., 1994 ; Nicola and Babon, 2015 ) ( Table 1 ).…”
Section: The Biology Of Lif and Lif Receptorsmentioning
confidence: 99%